2017
DOI: 10.1186/s12889-016-3914-z
|View full text |Cite
|
Sign up to set email alerts
|

Poor dietary diversity, wealth status and use of un-iodized salt are associated with goiter among school children: a cross-sectional study in Ethiopia

Abstract: BackgroundGlobally, more than two billion people are at risk of iodine deficiency disorders, 32% of which are school children. Iodine deficiency has been recognized as a severe public health concern in Ethiopia, however little is known about the problem. Therefore, this study aimed to assess the prevalence of goiter and associated factors among school children (6 to 12 years) in Dabat District, northwest Ethiopia.MethodsA school-based cross-sectional study was conducted from February 21 to March 31, 2016. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 32 publications
(45 reference statements)
7
40
2
1
Order By: Relevance
“…In this study setting, the prevalence of goiter was found to be 54.6 %, confirming that it is an endemic and severe public health problem. The finding was in line with the reported prevalence of Burie and Womberma district in Ethiopia (54.5%) [23], but higher than the reports from northwest Ethiopia, Metekel zone (39.5%) [26] and Dabat district (29.1%) [27].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study setting, the prevalence of goiter was found to be 54.6 %, confirming that it is an endemic and severe public health problem. The finding was in line with the reported prevalence of Burie and Womberma district in Ethiopia (54.5%) [23], but higher than the reports from northwest Ethiopia, Metekel zone (39.5%) [26] and Dabat district (29.1%) [27].…”
Section: Discussionsupporting
confidence: 91%
“…The other reason could be related to the time of study. Those studies conducted in other parts of Ethiopia and cited here [26,27] were done after the implementation of USI program in the country in 2011. Therefore; the program implementation and enforcement might have contributed to the reduction of goiter prevalence in some accessible areas of the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 out of 10 children) (Abebe et al). 17 Contrary to this, lower figures of IDD was reported in a study conducted in Saudi Arabia, (Al Dakheel, et al). 18 Abuye et al, in Ethiopia, reported 23% higher prevalence of Goiter among children of low income family than the family having higher income.…”
Section: Discussionmentioning
confidence: 78%
“…Hal ini sejalan dengan penelitian yang dilakukan oleh Abebe et al pada tahun 2017 di Ethiopia yang menunjukkan bahwa tidak terdapat hubungan antara besar keluarga dan pekerjaan orangtua dengan kejadian GAKY pada anak usia sekolah 10 . Penelitian lain yang dilakukan oleh Hariyanti dan Indrawati pada tahun 2013 di Kabupaten Ngawi menunjukkan bahwa tidak ada hubungan antara pendidikan orangtua dengan kejadian GAKY pada anak usia sekolah 11 .…”
Section: Hasil Dan Pembahasanunclassified